2013
DOI: 10.1590/s1806-00132013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de desnutrição e dor em pacientes admitidos pelo serviço de triagem em hospital oncológico

Abstract: BACKGROUND AND OBJECTIVES: Pain is a symptom influencing several aspects of daily life. This study aimed at early identifying pain in cancer patients, at evaluating how this symptom has interfered with food ingestion and its impact on patients' nutritional status. METHODS: This was a prospective study including 222 cancer patients referred to the screening service of a hospital. Participants have answered a questionnaire with questions about food ingestion, presence of current pain and pain in the last month, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…Direct involvement by the tumor is the most frequent cause of cancer patients' pain (70%), however in 17% of patients pain is related to the anti-tumor treatment itself 11 . It was observed that 75% of patients had severe pain (between 8 and 10), similar to Silva et al 12 , findings, where 63% of adult cancer patients had moderate pain in the first day of the study. In EMADOR, with regard to acute pain, most frequent descriptors were deep, intense, unbearable, desperate and blinding.…”
Section: Discussionsupporting
confidence: 88%
“…Direct involvement by the tumor is the most frequent cause of cancer patients' pain (70%), however in 17% of patients pain is related to the anti-tumor treatment itself 11 . It was observed that 75% of patients had severe pain (between 8 and 10), similar to Silva et al 12 , findings, where 63% of adult cancer patients had moderate pain in the first day of the study. In EMADOR, with regard to acute pain, most frequent descriptors were deep, intense, unbearable, desperate and blinding.…”
Section: Discussionsupporting
confidence: 88%
“…Constatou-se que, à medida que a intensidade da dor aumenta, ocorre uma intensificação correspondente na interferência no sono, comprometendo significativamente a capacidade do paciente de obter um repouso adequado (Silva et al, 2013). Os autores destacam que a persistência da dor não tratada está correlacionada não apenas a problemas físicos, mas também a sintomas de ansiedade e depressão, impactos nas atividades diárias e sociais, e, notadamente, prejuízos à qualidade do sono.…”
Section: Dor E Qualidade De Vidaunclassified
“…This descriptive study was conducted with geriatric cancer patients receiving treatment in the ambulatory chemotherapy outpatient clinic of a university hospital and in an oncology hospital. The results of a previous study were used to calculate the sample size of the study (5,18). Necessary minimum sample size was calculated to be 215 with α=0.05 and the test power of (1-β) 0.80.…”
Section: Design and Samplementioning
confidence: 99%
“…As is known, cancer patients intensely experience symptoms related to treatments such as anorexia, cachexia, taste changes, pain and malnutrition, besides symptoms caused by the disease process (15)(16)(17). Especially pain may prevent nutrition and lead to poor nutrition and malnutrition (18). Pain and malnutrition in elderly cancer patients should be routinely evaluated by nurses with appropriate assessment tools specific to the elderly individual, and pharmacological and non-pharmacological methods should be used in treatment (3).…”
Section: Introductionmentioning
confidence: 99%